2014
DOI: 10.1508/cytologia.79.151
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Associations of Chromosomes Due to Structural Heterozygosity in the Wild Plants of <i>Achillea millefolium </i>L. from Northwest Himalayas (India)

Abstract: Summary Presently, A. millefolium, a morphogenetically variable species, has been scored from phytogeographically isolated and unexplored areas of the northwest Himalayas for chromosome counts and male meiotic course. All the studied accessions shared the same meiotic chromosome number of n = 9 and existed at diploid level. A majority of the accessions exhibited the normal meiotic course including microsporogenesis and almost cent per cent pollen fertility. However, three accessions scored from Sangla Valley (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
5
13
0
Order By: Relevance
“…In the species, there seems to be a direct correlation of pollen sterility with structural heterozygosity. Similar effects of structural heterozygosity resulting in non-viable pollen grains has been reported in a number of plants, namely, Chrysanthemum zawadskii (Kim et al 2008), Artemisia parviflora (Gupta et al 2010), Astragalus chlorostachys (Rana et al 2012), Saxifraga diversifolia (Kumar and Singhal 2013), Achillea millefolium (Singhal et al 2014) and Anemone rivularis (Kumar et al 2015). Gohil and Koul (1978) and Sharma and Gohil (2003) have reported that structural heterozygotes of Allium consanguineum and A. roylei depicted complete gametic sterility due to reciprocal translocations, respectively.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In the species, there seems to be a direct correlation of pollen sterility with structural heterozygosity. Similar effects of structural heterozygosity resulting in non-viable pollen grains has been reported in a number of plants, namely, Chrysanthemum zawadskii (Kim et al 2008), Artemisia parviflora (Gupta et al 2010), Astragalus chlorostachys (Rana et al 2012), Saxifraga diversifolia (Kumar and Singhal 2013), Achillea millefolium (Singhal et al 2014) and Anemone rivularis (Kumar et al 2015). Gohil and Koul (1978) and Sharma and Gohil (2003) have reported that structural heterozygotes of Allium consanguineum and A. roylei depicted complete gametic sterility due to reciprocal translocations, respectively.…”
Section: Discussionsupporting
confidence: 70%
“…The accessions with higher percentage of chromosomes involved in translocations showed higher values of chiasma frequency and thereby increased recombination value. Kumar and Singhal (2013) in Saxifraga diversifolia, Singhal et al (2014) in Achillea millefolium, and recently Kumar et al (2015) have also found direct correlation between chiasma frequency and incidence of translocations. The existence of heterozygosity for translocations in the tetraploid taxon indicates that the species is quite active and has exploited structural chromosomal alterations to create specific gene combinations in addition to intraspecific polyploid chromosomal races (2x, 3x, 4x) and B-chromosomes.…”
Section: Discussionmentioning
confidence: 86%
“…In the presently studied accession of Tanacetum artemisioides, the majority of the PMCs showed the adjacent type of orientation of quadrivalents/hexavalents (ring or chain) and the alternate (zigzag) orientation was seen in only one PMC, resulting in a considerable amount of pollen sterility (30-35%), which appears to be the result of duplications and deficiencies of genes as mentioned by Ghosh and Datta (2006) in Nigella damascene. Similar effects of structural heterozygosity leading to nonviable pollen grains have been reported in a number of plants, namely, Citrus jambhiri (Singhal and Gill 1981), Chrysanthemum zawadskii (Kim et al 2008), Artemisia parviflora (Gupta et al 2010), Astragalus chlorostachys (Rana et al 2012), Saxifraga diversifolia (Kumar and Singhal 2013), Tradescantia spathacea (Koul et al 2013), Achillea millefolium (Singhal et al 2014), and Anemone rivularis (Kumar et al 2015). Gohil and Koul (1978) and Sharma and Gohil (2003) have reported that structural heterozygotes of Allium consanguineum and A. roylei depict complete gametic sterility due to reciprocal translocations.…”
Section: Discussionsupporting
confidence: 55%
“…From this laboratory, the naturally occurring reciprocal translocations have been reported in individuals of Artimisia parviflora (Gupta et al 2010), Astragalus chlorostachys (Rana et al 2012), Saxifraga diversifolia (Kumar and Singhal 2013), Achillea millefolium (Singhal et al 2014), and Anemone rivularis (Kumar et al 2015). Kaul (1977) opined that breakage and exchange of heterologous chromosomes in a structural heterozygote are genetically conditioned and controlled, thereby eliminating the chance factor operating for the predominance of either ring or chain or both types of multiple associations of chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, 50% non-viable gametes are produced toward pollen side and 50% toward ovule side. Such a phenomenon of structural heteozygosity leading to some sterility of pollen grains has been reported in a number of cases namely, Chrysanthemum coronarium (Gill and Gupta 1981), C. zawadskii (Kim et al 2008), Lathyrus boissieri (Ghaffari et al 2009), Artemisia parviflora , Euphorbia pilosa (Saggoo and Farooq 2011), Astragalus chlorostachys (Rana et al 2012), Tradescantia spathacea (Koul et al 2013), Saxifraga diversifolia (Kumar and Singhal 2013), Achillea millefolium (Singhal et al 2014) and Anemone rivularis (Kumar et al 2015). Complete male sterility due to reciprocal translocations has also been reported in Allium consaguineum (Gohil and Koul 1978) and Allium roylei (Sharma and Gohil 2003, Kohli and Gohil 2011, Kohli and Koul 2013.…”
Section: Resultsmentioning
confidence: 90%